Yasadipura I (1729-1803) Biografi dan Karya- Karyanya - Hamid Nasuhi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
Yasadipura's (I) works was wll known by Javanese noble (priyayi) since 19th until the beginning of 20th, much of them are re-written, analyzed, and re-interpretated. His works need to be analyzed and understood morelike what Ricklefs has done soundly in analyzing of the authenticity of the Java manuscripts which much spread in manylibraries and museum both in Indonesia and abroad